Optimization of Organisational Processes Through Robotic Process Automation (RPA): A Systematic and Methodological Approach - Mirabete, Martín (2024)
The study explores Robotic Process Automation (RPA) as a key technology for improving organizational efficiency by automating repetitive and rule-based tasks. It presents a systematic and methodological approach to RPA implementation, focusing on its tangible and intangible benefits and the challenges faced during adoption. A detailed literature review forms the foundation of this analysis, emphasizing key considerations such as process selection, metrics, and complexity. A practical case study highlights the successful use of RPA in automating the collection of prices for the Basic Food Basket, demonstrating its efficiency in reducing costs and improving accuracy. The research underscores RPA's significant potential to streamline operations and enhance productivity across various sectors. Future research should explore the integration of RPA with artificial intelligence to enable more intelligent automation solutions.